2016
DOI: 10.1007/s12529-016-9555-x
|View full text |Cite|
|
Sign up to set email alerts
|

The Prevalence, Attitudes, and Correlates of Waterpipe Smoking Among High School Students in Iran: a Cross-Sectional Study

Abstract: Background: Waterpipe (WP) smoking is a growing public health concern. However there is little information concerning the prevalence, knowledge, attitudes and cessation of WP smoking among high school students in Iran.Purpose: To determine the correlates of WP smoking among 15-17 year-old high school students in Iran.Methods: Data were collected using the Global Youth Tobacco Survey (GYTS), a selfadministrated questionnaire distributed to a representative sample of high school students aged 15-17 in the city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…There is a potential for increased usage and hence increased tobacco-related morbidity and mortality unless intervention measures are taken now 11 . In a study, 9.7% of the students consumed waterpipe in the past month, of which 66.6% were male and 33.4% were female, which indicates a higher prevalence in males 4 . In another study, the prevalence of current WPS was reported as 26.3% among male high school students 12 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is a potential for increased usage and hence increased tobacco-related morbidity and mortality unless intervention measures are taken now 11 . In a study, 9.7% of the students consumed waterpipe in the past month, of which 66.6% were male and 33.4% were female, which indicates a higher prevalence in males 4 . In another study, the prevalence of current WPS was reported as 26.3% among male high school students 12 .…”
Section: Introductionmentioning
confidence: 97%
“…For example, lung cancer, respiratory diseases, low birth weight, periodontal disease, bladder cancer, nasopharyngeal cancer, oesophagal cancer, oral dysplasia, infertility and hepatitis C infection 3 are all attributed to WPS. It is estimated that approximately 100 million people, particularly teenagers, use this kind of smoking 4 . Since the period 2009-2016, studies reporting on WPS indicated a 0.4% to 2.9% annual increase in current WPS in the Eastern Mediterranean and European Regions, and 0.3% to 1.0% increase in the USA [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, thirty high-schools, including sixteen girls' and fourteen boys' high-schools, and ninety classes (grades 9 to 11) [30] were chosen to participate in the study. The full details of the methodology have been reported earlier [31,32].…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…Studies reported that its prevalence among young women is 6.3% in the United States (13) and 41% in Pakistan (14). WTS is also a significant public health challenge in Iran and is the most common method for tobacco smoking by adolescent and young women (15)(16)(17). Studies in Iran reported that WTS prevalence ranged from 7.1% (18) to 38.9% (19) among adolescents and was 11.5% among female university students (20).…”
mentioning
confidence: 99%